RdRp (RNA-dependent RNA polymerase): A key target providing anti-virals for the management of various viral diseases - Pathania Shelly; Rawal Ravindra K; Singh Pankaj Kumar (ELSEVIER, 2022)
With the arrival of the Covid-19 pandemic, anti-viral agents have regained center stage in the arena of medicine. Out of the various drug targets involved in managing RNA-viral infections, the one that dominates almost all RNA viruses is RdRp (RNA-dependent RNA polymerase). RdRp are proteins that are involved in the replication of RNA-based viruses. Inhibition of RdRps has been an integral approach for managing various viral infections such as dengue, influenza, HCV (Hepatitis), BVDV, etc. Inhibition of the coronavirus RdRp is currently rigorously explored for the treatment of Covid-19 related complications. So, keeping in view the importance and current relevance of this drug target, we have discussed the importance of RdRp in developing anti-viral agents against various viral diseases. Different reported inhibitors have also been discussed, and emphasis has been laid on highlighting the inhibitor's pharmacophoric features and SAR profile. (c) 2021 Elsevier B.V. All rights reserved.